2021
DOI: 10.1055/s-0041-1723034
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Granulocyte-Colony Stimulating Factor to Treat Acute-on-Chronic Liver Failure

Abstract: Patients with acute-on-chronic liver failure (ACLF) have a devastating prognosis and therapeutic options are limited. Granulocyte-colony stimulating factor (G-CSF) mobilizes immune and stem cells and possess immune-modulatory and proregenerative capacities. In this review, we aim to define the current evidence for the treatment with G-CSF in end-stage liver disease. Several smaller clinical trials in patients with different severity grades of end-stage liver disease have shown that G-CSF improves survival and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…[6][7][8][9] Bone marrow-derived stem cells have been shown to be potent in modulating immune functions and promoting regenerative capacities, thus mitigating various types of liver injury in experimental and clinical studies. [10][11][12] However, costs, high technical requirements and peri-interventional complications limit the general applicability of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Bone marrow-derived stem cells have been shown to be potent in modulating immune functions and promoting regenerative capacities, thus mitigating various types of liver injury in experimental and clinical studies. [10][11][12] However, costs, high technical requirements and peri-interventional complications limit the general applicability of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…For example, therapeutic agents targeting inflammation and fibrosis in NASH, CCR2/CCR5, TLR4, ASK1 and lysine oxidase were considered ineffective in recent clinical trials to alleviate endpoint outcomes in NASH, particularly fibrosis [ 10 , 338 ]. Furthermore, although several smaller clinical trials in patients with end-stage liver disease of varying severity have shown that G-CSF improves patient survival and reduces complications [ 339 ]. However, in a recent multicenter controlled trial, G-CSF did not have a significant beneficial effect in patients with chronic acute liver failure, suggesting that it should not be used as standard of care for end-stage liver diseases [ 340 ].…”
Section: Current Status Of Immunotherapy For Liver Diseasesmentioning
confidence: 99%
“…However, results from small trials were positive but larger multicentre European studies have not shown survival benefit [83][84][85] . Inhibition of TLR4 combined with G-CSF application is a novel combinatorial approach that improves mortality, tissue injury, and reduces cytokine levels in animal models of ACLF 86 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%